Project-Based Learning vs. Problem-Based Learning: Uncovering Effective Learning Methods - Ditya Lazuardy Ramadhan; Dzurrotun Nafisah (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Effective education must target dynamic and adaptive learning abilities. Two methods learning that is proven to be effective in developing students' creativity and critical thinking are Project-Based Learning (PBL) and Problem-Based Learning (PBM). Project-Based Learning involving students in completing real projects that are relevant to everyday life, increasing student motivation, collaboration and critical thinking. This approach allows students apply academic concepts in practical contexts, strengthen understanding, and develop a sense of responsibility and ownership of their learning outcomes. On the other hand, Problem-Based Learning focuses on developing students' abilities to solve problems complex and realistic. This process not only improves critical thinking and abilities problem solving, but also collaboration and communication skills. PBM often involves real world situations, making learning more relevant and interesting for students. These two methodshas advantages in improving academic outcomes and developing life skills student. Educators can choose or combine both to create a learning environment holistic approach that suits the characteristics and needs of students. Therefore, it is important for modern education to use dynamic and responsive learning models such as PBL and PBM to help students become competent, creative and independent in completing challenges in the future. Everything is returned to the students, whichever is more effective both of them.